2016 IEEE 2nd International Conference on Big Data Security on Cloud (BigDataSecurity), IEEE International Conference on High P 2016
DOI: 10.1109/bigdatasecurity-hpsc-ids.2016.73
|View full text |Cite
|
Sign up to set email alerts
|

OwlSight: Platform for Real-Time Detection and Visualization of Cyber Threats

Abstract: Abstract-Security reports published by leading companies reveal the growing number of cyber attacks. Thefts of money or sensitive data, harm the reputation of organizations and sabotage of national critical infrastructures are some of the motivations behind these attacks. The sophistication of these attacks is very high, creating major challenges to the detection and mitigation in useful time. In this context the development of systems to provide situational awareness, to detect cyber threats and alert them in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
0
10
0
2
Order By: Relevance
“…In our review, we observed that quite a large number of countermeasures are either not evaluated at all ( [23], [40], [45] , [48] , [49] , [62] , [75] , [88] , [91] , [67] , [92] , [105] , [110], [111], [114], [137], [141], [154], , [160], [174], , [175]) or evaluated weakly ( [60], [70], [100], [109], [132], [138], [147], [158], [161], [165], [171]). We consider an evaluation as weak evaluation when the system is evaluated with a small dataset (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our review, we observed that quite a large number of countermeasures are either not evaluated at all ( [23], [40], [45] , [48] , [49] , [62] , [75] , [88] , [91] , [67] , [92] , [105] , [110], [111], [114], [137], [141], [154], , [160], [174], , [175]) or evaluated weakly ( [60], [70], [100], [109], [132], [138], [147], [158], [161], [165], [171]). We consider an evaluation as weak evaluation when the system is evaluated with a small dataset (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Carvalho et al [160] present an approach for real-time detection of attacks on an organization's network based on analysing a large amount of malware data gathered from various resources on daily basis. The proposed system, OwlSight, works in seven steps; (1) OwlSights collects malware data from both external (Social media data) and internal sources (organizational network flow and logs) (2) Gathered data is brought into a single format (3) Data is clustered into events based on similarity (4) Duplicate copies are removed (5) Data is enriched by analysing it for locations, numbers, names, and URLs (6) Data for each event is stored in a separate database (Email DB, and Social media DB) (7) Big data analysis engine is used to analyse these databases and show real-time alerts to the security administrators of an organization.…”
Section: Network + Host-based Anomaly Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…OwlSight [9] birden fazla istihbarat kaynağından büyük hacimde veri toplayıp bunları analiz eden bir sistemdir. Günlük 107'den fazla kötü amaçlı yazılımın ne zaman ortaya çıktığını, ne kadar yayıldığını, ait olduğu aile sınıfını ortaya çıkartan ve bu verileri görselleştirerek düşük yanlış alarm sayısına sahip gerçek zamanlı bir uyarı sistemi oluşturmaktadır.…”
Section: İlgi̇li̇ çAlişmalarunclassified
“…A cyber threat platform for real-time detection and visualization of cyber threats OwlSight is presented in [2]. The platform is composed by several building blocks and it is able to collect huge amounts of data from multiple sources, prepare and analyze the data and present the findings through a set of insightful dashboards.…”
Section: Introductionmentioning
confidence: 99%